Interrogating Political Party Institutionalisation In Nigeria’s Fourth Republic - Yusuf, Isah Musa (Kashere Journal of Politics and International Relations, 2025)
Even though political parties have proliferated in Nigeria since former head of state Abdulsalami Abubakar successfully handed over power to a democratically elected government in 1999, their character and operations leave much to be desired. They are faced with a plethora of contradictions which negate their roles in Nigeria's democratic project. Some of these challenges include (but not restricted to) lack of ideology, absence of institutionalized parties, manipulation of ethnicity and religion by the elites, political violence, God fatherism and profound lack of intraparty democracy. The paper adopts Mainwaring’s dimensions of party system institutionalisation as its framework of analysis. Secondary data were collected and analysed using descriptive analysis. The paper identified ideological deficit, lack of internal party democracy and unprincipled inter and intra party conflicts as constituting serious drawbacks to the institutionalisation of political parties in Nigeria. The work recommends increased organisational vitality through internal party cohesion, strong and focused party leadership and more informed civic education to curb the trend. The political elites must learn to play the game by the rules.